Metode McCall’s untuk Pengujian Kualitas Sistem Informasi Administrasi Tugas Akhir (SIATA) - Christina Juliane; Rizal Dzulkarnaen; Windi Susanti (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Department of English, Politeknik Negeri Bandung applies the Information System of Final Project Administration to aid the final assignment administration management. However, when the system is applied some new problems appear. The problems affect the ongoing performances of administrative services. This study aims to analyze and test the quality of SIATA to find out the occurring problems and factors that influence SIATA’s quality. This study uses McCall’s method to measure the quality of software and its product. This analysis method is used to acquire specific problems. The analysis was conducted on product operation aspects consisting of quality factors of correctness, reliability, efficiency, integrity, and usability. Data were collected using questionnaires from 58 respondents comprised of lecturers, students, and administrative staff of the Department of English, Politeknik Negeri Bandung. The results of the research showed that the overall SIATA’s quality stood at the level of 55,22% (the quality was fairly good based on the scales of criteria to interpret the percentages of quality factors). The research comes up with some recommendations that can be used to improve the performance of SIATA’s quality.